Mechanical properties and oxidation resistance of Y containing CrAlN-based hard coatings - Muhammad Hafiz Aziz (2016)
The addition of yttrium into CrN and CrAlN coatings is known to improve the oxidation resistance and thermal stability of the coatings at temperatures above 1000ºC. However, the right amount of yttrium content to be doped is not known from past research. Hence, the aim of this project is to evaluate the thermal stability and the oxidation resistance of CrAlYN coatings with four different yttrium content in addition to the CrN and CrAlN coatings to identify the right amount of yttrium to be doped into the coatings. The coatings were deposited by a HiPIMS Plasma Vapour Deposition machine rotating at 3rpm for 9000s. Following that, Rockwell-C Indentation, Scratch tests, Nanoindentation, heat treatment in oxygen and argon chambers, and X-Ray Powder Diffraction were carried out on the coating samples to obtain properties such as adhesion, hardness, young’s modulus and oxidation resistance. It was found that the CrAlYN with mid yttrium content have the best oxidation resistance compared to its other counterparts at 800ºC as seen from its XRD patterns. The CrAlYN with mid yttrium content coating hardness also dropped from ~24GPa to ~21GPa, the least compared to the other coatings after annealing at 1100ºC. The adhesion from the Rockwell-C Indentation showed that CrAlYN (mid Y) has a slightly poor adhesion compared to the CrN and CrAlN. However from the Scratch Test, its critical load, Lc1, indicates that it adhesion does improve slightly with the addition of the right amount of yttrium. The difference in result of adhesion from the Rockwell Indentation and Scratch Test result was due to the direction of grain growth and internal stresses of the coatings during the deposition process. In all, the results indicates a very promising applicability of the CrAlYN (mid Y) coating for high speed machining at high temperature environments.